If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y=-1(-2)+2
We move all terms to the left:
y-(-1(-2)+2)=0
We add all the numbers together, and all the variables
y-4=0
We move all terms containing y to the left, all other terms to the right
y=4
| 12=4500m | | -87=7(x-4)-3 | | 540=5x+104+116+120 | | 2x+4x+3=21 | | –g+7=g−9 | | 42+f=150 | | 19p-10=34p+5 | | -6k+2k-1=-6k-9 | | P=4r | | y=-1(-3)+2 | | 12-2x=21+5x | | 7m-4=88 | | 10xx3=-33 | | 15/y=8/13 | | -8n+2=2(7-2n) | | s-13=46 | | -6j=90 | | 7x–12+4x=10 | | Y=20x+ | | -2x+46=-16+2x | | x/3+21=27 | | 13=x+11+3x+12 | | 9-2c=-3 | | n-57=8 | | 17×51=n | | 2x4+-5x2+7=0 | | 8j=-11 | | -6c+13=-17 | | 13x-7x+35=35+6x | | 2.34x-1.8=-4.5 | | 10m+6=68 | | 88=s+83 |